(untitled) (World Economics and Finance Bulletin, 2022)
The banking sector is one of the important sectors as it represents a major link in the development of the financial system in any country. The risks to which the banking sector is exposed have varied greatly, including the credit risks, which result from these risks are the risks of customers not paying their obligations towards the bank and thus lead to the bank’s exposure to significant losses as a result of bad debts and an increase in allocations for doubtful debts. Therefore, the research problem revolves around the question (what is the effect of credit risk on the financial performance of the Bank of Baghdad, as a sample for research)